The Influence of Family Support on Medication Adherence in Pulmonary TB Patients at the Tenayan Raya-Riau Community Health Center in 2023 - Lestari, Yani (Jurnal EduHealth, 2022)
Pulmonary Tuberculosis is an infectious disease that is spread throughout the world and has become a public health problem, even in 2015, WHO declared pulmonary TB a global emergency. Based on the health profile of North Sumatra Province, in 2023, the prevalence of pulmonary TB was recorded at 13,833 sufferers, with a prevalence rate of 116.1 per 100,000 population. In the process of curing pulmonary TB, the important role of the family as the closest unit to the sufferer is needed, so that family knowledge and perceptions about pulmonary TB include: understanding, causes, signs and symptoms, methods of transmission, methods of care and treatment, as well as ways to prevent pulmonary TB are very much needed by the family. to support the healing process for pulmonary TB sufferers in the family. The aim of this research is to determine the relationship between family support and medication adherence in pulmonary TB patients at the Tenayan Raya Community Health Center in 2023. The type of research used is correlation with a cross-sectional study design. This research was conducted at the Tenaya Raya Health Center, the research was carried out April-August 2023. The research population was 30 people. Sampling in this study used a total sampling technique of 30 people. The results can be seen that 13.3% of respondents had insufficient family support but were not compliant and 3.3% were compliant, 23.3% of respondents had sufficient family support but were compliant, 60% of respondents had good family support but were compliant. The results of analysis using the chi-square test obtained a p value = 0.000.